The block-by-block method with Romberg quadrature for the solution of nonlinear volterra integral equations on large intervals - Katani, R.; Shahmorad, S. (Український математичний журнал, 2012)
We investigate the numerical solutions of nonlinear Volterra integral equations by the block-by-block method especially useful for the solution of integral equations on large-size intervals. A convergence theorem is proved showing that the method has at least sixth order of convergence. Finally, the performance of the method is illustrated by some numerical examples.